Cost effectiveness of journalism education in a small nation state - Harro-Loit, Halliki (Žurnalistikos tyrimai, 2009)
The article discusses the role of journalism as a discipline in a small nation state and provides analysis of the economic factors that influence the journalism programs. The article discusses some of the economic aspects of journalism education at the academic university and provides a case study on the basis of the two programs provided by the University of Tartu: Bachelor (BA) and Master’s (MA) programs. The curricula are held by the Institute of Journalism and Communication.Keywords: journalism curriculum, education, cost, small market.p>